Dramaturgy and performance - Turner, Cathy (Palgrave, 2016)
Outlining different perspectives, this classic and field-defining text introduces 'dramaturgy' as a critical concept and a practical process in an accessible and engaging style. The revised edition includes a new introduction and afterword which provides insight into contemporary developments and future directions of scholarship.